Experimental investigation on enhanced microscale heat transfer - inverted fish scale channel - Lim, Teck Siang (2015)
The introduction of micro-channel heat sink significantly increases the efficiency and effectiveness of heat dissipation due to its high heat transfer effect. However this technology is not widely utilized due to its high cost in fabrication. This research presents the enhanced microscale heat transfer effect by combining two macro geometries, which may be fabricated with less complexity and at lower cost. An annular micro-channel of 300 micrometer gap is formed by insertion of a cylindrical stainless steel insert with 19.4mm outer diameter into a copper pipe with inner diameter of 20.0mm. Effects of Inverted Fish Scale (IFS) insert on heat transfer coefficient and pressure drop were examined based on the ratio of insert profile height (e) to channel height (H), and ratio of insert pitch length (P) to insert profile height (e) at heat flux of 1000W ranging from 2.0 L/min to 8.0 L/min. For IFS insert with different e/H ratio, the results show that the average heat transfer effect is higher at higher e/H ratio. The highest heat transfer coefficient was achieved by e/H=0.7, which recorded the absolute value of 35.4 kW/m²•K at 5.5 L/min, corresponding to pressure drop of 1.887 bar. For e/H=0.7, the enhancement of heat transfer coefficient is roughly doubled when compared to Plain insert at each Reynolds number. In the study of P/e ratio, the highest average heat transfer coefficient was achieved by P/e=5 at 5.5 L/min, which was 36.01 kW/m²•K, with the pressure drop of 2.918 bar. Similarly, e/H=0.7 offers double heat transfer enhancement when compared to Plain insert at each Reynolds number. Future research should focus on finding the optimal relative enhancement of heat transfer effect to pressure drop increment for IFS insert by altering insert profile parameters based on this research finding. New nature-inspired insert profiles which can be manufactured at low costs and achieve better heat transfer and hydrodynamic performance compared to IFS insert design are encouraged.